Financial Education and its influence among 1st and 2nd year High School students in public schools (Research, Society and Development, 2022)
Financial education makes it possible for citizens to go through learning processes that lead them to make conscious purchases and learn to manage their income, avoiding unnecessary expenses, and encouraging conscious and healthy consumption, in the act of consumption, individuals commit to financial decisions and commitments leading to indebtedness. Faced with the need to train financially conscious citizens, especially among young people, the present research aims to know if the level of financial education of young people influences their purchase decision process, based on students from the 1st and 2nd year of high school in public schools in the city of Porto Velho, capital of the state of Rondônia, through their financial decision-making in everyday situations. The theoretical foundation was based on studies by Kahneman and Tversky, called Perspective Theory, and on OECD research. The research was characterized as applied, descriptive, with a quali-quantitative approach, being outlined through a Survey type survey, through a sample, of the non-probabilistic type, and for data collection an electronic questionnaire elaborated on the Google platform was used. Forms. The present study made it possible to understand that students have low levels of knowledge about financial education, but they make conscious decisions about everyday cases. It is noteworthy that the school environment does not propagate issues related to personal finance, however, the family environment is a driver of this theme.